Pelatihan Penulisan Karya Ilmiah Untuk Guru Sma Kartikatama Kota Metro - Qomariah, Siti; Rosyidah, Ummi; mariana, erni; Wardany, Kusuma; Kinasih, Ayang; Utami, Endang Sri (STMIK Royal, 2023)
Abstract: Scientific work can be used by teachers as a facility for communicating new information, ideas, studies, and research results to the general public. The preparation of scientific papers is very meaningful for the professional development of teachers, but in reality, the culture of writing scientific papers among teachers is still low. Meanwhile, the teacher can write scientific papers based on the implementation of the teacher's creativity and criticality in the daily activities that are observed and experienced in creating a better quality of education to achieve maximum learning results. This program aims to conduct training in the preparation of scientific papers in this matter scientific postings for teachers of SMA Kartikatama Metro. This program is carried out using a classical approach which is tried by giving lectures and delivering modules and individual approaches are tried when accompanying participants in writing scientific papers. Achievement of the target number of participants as well as the objectives of this training can be assessed as good. Within 2 weeks as many as 3 teachers have tried to write scientific posts. All the modules that have been planned can be informed to the participants, even though there are many time constraints there are some modules that are informed in an outline. The expertise of the participants can be seen from the ability to compose scientific papers that can be considered good.Keywords: scientific work; teacher; training. Abstrak: Karya ilmiah dapat digunakan guru sebagai fasilitas mengomunikasikan informasi baru, gagasan, kajian, serta hasil riset kepada khalayak umum. Penyusunan karya ilmiah sangat berarti untuk pengembangan keprofesionalan guru, tetapi pada kenyataannya budaya menulis karya ilmiah di kalangan guru masih rendah. Sementara itu guru bisa menulis karya ilmiah bersumber pada implementasi kreatifitas serta kekritisan guru terhadap kegiatan tiap hari yang diamati serta dialaminya dalam menciptakan mutu pendidikan yang lebih baik sehingga menggapai hasil belajar yang maksimal. Tujuan program ini merupakan melakukan pelatihan penyusunan karya tulis ilmiah dalam perihal ini postingan ilmiah untuk guru SMA Kartikatama Metro. Program ini dilaksanakan memakai pendekatan klasikal yang dicoba dengan membagikan ceramah serta penyampaian modul serta pendekatan individual dicoba pada saat mendampingi peserta dalam menulis karya ilmiah. Ketercapaian sasaran jumlah partisipan serta tujuan pelatihan ini bisa dinilai baik. Dalam kurun waktu 2 pekan sebanyak 3 orang guru sudah berupaya menulis postingan ilmiah. Seluruh modul yang sudah direncanakan bisa di informasikan kepada paserta, walaupun terdapat banyak keterbatasan waktu terdapat sebagian modul yang di informasikan secara garis besar. Keahlian paserta dilihat dari kemampuan menyusun karya ilmiah yang dapat dinilai baik.Kata kunci: guru; karya ilmiah; pelatihan.